Perception of Religion in Azerbaijani Life Science Textbooks: Quantitative and Qualitative Analysis - Azizova, Elnura (Scholarya Demo Journal of Ruby, 2018)
Compulsory religious courses are not taught in primary and secondary schools of the Republic of Azerbaijan. Religious knowledge is provided to students within the framework of Life Science courses taught in primary and secondary education (grades 1-9). School students study the basics of the world religions as a core part of Azərbaycanın orta ümumtəhsil məktəblərinin "Həyat bilgisi" dərsliklərində dinə baxış... 29 the general worldview in the first place. On the other hand, they master universal ethical and moral values as a principal part of their school education in a systematic way. The purpose of this article is to examine perception of religion in Life Science textbooks that covers the grades ranging from the first to the ninth. These textbooks are analyzed on the basis of their methods, content and visuals used for the representation of religion/s for the 6-15 age group. Quantitative content analysis and qualitative subject analysis are utilized in the study. The information about religion is classified from various standpoints. The following questions are analyzed by the qualitative method: How is the religion, as a whole represented in Life Science textbooks? What specific language is used for representing the religion/s? Are the religions represented through the sectarian approach? To what extent is the specific religious demography of Azerbaijan considered?